Korelasi Topologi Geometris Tapak Bangunan terhadap Tingkat Kerusakan Pasca Gempabumi dan Tsunami 2018 di Sebagian Kota Palu melalui Analisis Statistik Geospasial - Yunifar Susanto D Madusila; Danang Sri Hadmoko; Iswari Nur Hidayati (Buletin GAW Bariri (BGB), 2026)
The 2018 Palu earthquake and tsunami caused extensive building damage, particularly along the coastal areas of Palu Bay. One factor influencing the severity of damage is the geometric topology of building forms. This study aims to classify the geometric topology of buildings and analyze the relationship between building geometric forms and damage levels using data from Copernicus EMS Rapid Mapping and OpenStreetMap (OSM). A spatial overlay method was applied to link building footprints with damage levels, while both damage and geometric classification were validated using high resolution WorldView–2 imagery. Statistical analysis using the Kruskal – Wallis H test and Dunn’s post hoc test revealed a significant influence of building shape on damage level p – value < 0.05, where irregular building shapes other shapes tend to be more vulnerable to severe damage. In addition to building geometry, damage levels are also influenced by location – related factors, particulary proximity to the coastline, elevation, and tsunami inundation height. Therefore, more regular geometric buildings forms, such as rectangular and square shapes, are recommended as considerations in building design and settlement planning in earthquake and tsunami prone areas.